2018
DOI: 10.17860/mersinefd.434785
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Eleştirel Düşünme Eğilimi ile Liderlik Yönelimleri Arasındaki İlişki

Abstract: Bu araştırmanın amacı, öğretmen adaylarının eleştirel düşünme eğilimi ile liderlik yönelimleri arasındaki ilişkiyi belirlemektir. Araştırma, nicel yaklaşıma uygun olarak tarama deseninde, 2017-2018 akademik yılı bahar döneminde Ankara Üniversitesi Eğitim Bilimleri Fakültesi ve Kafkas Üniversitesi Eğitim Fakültesi'nde psikolojik danışma ve rehberlik ile sınıf öğretmenliği programlarında öğrenimlerine devam eden 405 öğretmen adayıyla gerçekleştirilmiştir. Araştırmada "Eleştirel Düşünme Eğilimi" ile "Liderlik Yön… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
9
0
4
Order By: Relevance
“…In the studies, in which the critical thinking dispositions of the pre-service teachers studying in different departments of the faculties of education are determined (Turnuklu & Yesildere, 2005;Korkmaz, 2009;Tumkaya 2011;Kucuk & Uzun,2013: Akyuzler, 2014: Can & Kaymakci, 2015Yildirim & Sensoy,2017;Aslan & Aybek, 2017;Ozdemir, Buyruk & Gungor, 2018), it is seen that the stakeholders in general have different and sometimes common ideas in many respects. For instance, in the study by Korkmaz (2009), "it was found that the education given in the Faculties of Education did not contribute as much to the level of critical thinking disposition of pre-service teachers, it was stated that the situations as the students' education had more theoretical dimensions, the students were generally hesitant in the learning and teaching environments, the choice of test type measurement tools in the evaluation activities, the fact that the activities, the lack of much emphasis on activities requiring analysis, synthesis and evaluation could have caused this result" (p.893).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies, in which the critical thinking dispositions of the pre-service teachers studying in different departments of the faculties of education are determined (Turnuklu & Yesildere, 2005;Korkmaz, 2009;Tumkaya 2011;Kucuk & Uzun,2013: Akyuzler, 2014: Can & Kaymakci, 2015Yildirim & Sensoy,2017;Aslan & Aybek, 2017;Ozdemir, Buyruk & Gungor, 2018), it is seen that the stakeholders in general have different and sometimes common ideas in many respects. For instance, in the study by Korkmaz (2009), "it was found that the education given in the Faculties of Education did not contribute as much to the level of critical thinking disposition of pre-service teachers, it was stated that the situations as the students' education had more theoretical dimensions, the students were generally hesitant in the learning and teaching environments, the choice of test type measurement tools in the evaluation activities, the fact that the activities, the lack of much emphasis on activities requiring analysis, synthesis and evaluation could have caused this result" (p.893).…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, gender was one of the background variables used in the studies we reviewed. Our analysis showed that while gender was a significant determinant of CTD of pre-service in some of the studies (2,7,12,13,21,23,25,31,35,40,51,62,63,65,74,79,84,85,88), more studies did not find any significant difference between gender and CTD scores of the participants (1,5,10,11,15,19,22,24,27,30,32,37,39,41,45,46,47,50,53,54,55,58,69,71,72,76,77,78,81,86). In addition, almost two-thirds of th...…”
Section: Independent and Background Variables Used In The Reviewed St...mentioning
confidence: 66%
“…To begin with the methodological results, our descriptive analysis revealed that most of the studies employed quantitative research designs (see Table 1). 2,3,7,11,12,13,16,18,19,20,23,24,28,32,34,35,37,40,41,43,46,47,48,50,52,54,55,56,60,63,65,67,68,70,71,72,73,78,81,87 Survey 5,8,10,15,21,22,25,27,31,33,36,…”
Section: Research Design Of the Reviewed Studiesmentioning
confidence: 99%
See 2 more Smart Citations